Comparative quantitative survey of patient experience in Barrett's oesophagus and other gastrointestinal disorders. Issue 1 (31st March 2020) - Britton, James; Taxiarchi, Paraskevi; Martin, Glen; Willert, Robert; Horne, Maria; Hamdy, Shaheen; McLaughlin, John; Ang, Yeng
Abstract : Objective: To assess health-related quality of life in patients with non-dysplastic Barrett's oesophagus (NDBO) and endoscopically treated dysplastic Barrett's oesophagus (DBO). Design: This quantitative, self-administered questionnaire study was conducted across three National Health Service hospitals. Data were collected from three other cohorts; gastro-oesophageal reflux disease (GORD), colonic polyp surveillance and healthy individuals. Fisher's exact and Spearman's rank correlation tests were used for analysis. Propensity score matching adjusted for age, sex and comorbidities. Results: 687 participants were eligible for analysis (NDBO n=306, DBO n=49, GORD n=132, colonic polyps n=152 and healthy n=48). 53% of NDBO participants reported similarly high cancer worry, comparable to DBO (50%, p=0.933) and colonic polyp participants (51%, p=0.355). Less cancer worry was reported in GORD participants (43.4%, p=0.01 vs NDBO). NDBO participants reported anxiety in 15.8% and depression in 8.6% of cases, which was similar to the other disease cohorts. Moderate or severe heartburn or acid regurgitation was found in 11% and 10%, respectively, in the NDBO cohort, comparable to DBO participants (heartburn 2% p=0.172, acid regurgitation 4% p=0.31) but lower (better) than GORD participants (heartburn 31% p=<0.001, acid regurgitation 25% p=0.001). NDBO participants with moderate or severe GORD symptoms were associated with higher rates of anxiety (p=<0.001), depression (p=<0.001) and cancer worry (p=<0.001). NDBO patients appropriately perceiving their cancer risk as low had lower rates of cancer worry (p=<0.001). Conclusion: This study provides insight into the problems Barrett's oesophagus patients may face. Future care pathways must be more patient focussed to address misconceptions of cancer risk, oesophageal cancer related worry and GORD symptom control.